Driving Digital Transformation: Lessons from Seven Developing Countries - Benno Ndulu; Elizabeth Stuart; Stefan Dercon; Peter Knaack (Oxford University Press, 2023)
This book traces the experience of digital economic transformation in seven developing countries, providing insights for policymakers and practitioners in similar situations as well as lessons for outsiders trying to support government reform efforts more broadly. In one country, the prime minister pushes for the liberalization of digital finance as a central pillar of the country's national strategy, while the central bank almost makes it a criminal offence. In another, the digital minister tries to scupper the very process to support digital transformation that the president has asked them to co-lead. This book gives a ringside seat on seven developing countries' tumultuous early steps on the path to a reform of the economy and the government using technology. Written by a group of academics and practitioners from Oxford at the heart of the process, but foregrounding the voices of the policymakers and participants, this book documents and critically assesses efforts to assist a set of governments to kick-start digital transformation. In doing so, it offers lessons for policymakers in other countries. But beyond that, it is an exposition of the process of policymaking more generally in the 2020s, and offers a broader insight as to how outsiders can play a sensible role in other reform processes in developing and emerging countries.
Keywords: 330; developing countries; development; digital; economic transformation; emerging economies; government reform; public policy; technology